Progress in understanding oral health and HIV/AIDS. (13th January 2014) - Patton, LL
<x xml:space="preserve">Abstract</x> Over the last 30 years, there have been significant advances in our scientific knowledge of HIV disease, including prevention, detection, medical management, and attempts at cure. Investigations and observations of the oral cavity in individuals with HIV disease have contributed substantially to scientific discovery and innovation. Challenges remain for managing existing and emerging oral diseases associated with HIV and understanding the contribution of latent oral mucosal reservoirs to HIV eradication.